Professors, Militance, and Professionalism - Haehn, James O. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This document presents the results of a survey of full-time faculty members at 4 California State Colleges. The survey was designed to discover the level of militancy within the faculty and to single out some other characteristics common to more militant professors. Highlights of the findings include: (1) Militant faculty are more likely to be in the disciplines associated with the Humanities and Social Sciences than in any of the other fields. (2) Militant professors are more likely to be those who view themselves as politically liberal or radical. (3) Although militant faculty members do not differ significantly from other professors in their educational perspectives, they do have a tendency to be more research than teaching oriented. (4) The militant instructors tend to function socially within more narrow circles than do nonmilitant professors, and this appears both in their contacts with faculty and students. (5) Militant faculty are less satisfied with their careers, with their institutions, and with the general character of college teaching. (6) The highly militant professors tend to be persons who have been in college teaching long enough to reach intermediate rank, and are not as likely to be among the older or younger groups of professors. (Author/HS)
ERIC Note: Paper presented at the Meeting of the Pacific Sociological Association (Portland, April, 1972).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Activism; College Faculty; Faculty; Higher Education; Professors; Teacher Militancy; Teacher Welfare